Comparative study of bacterial infection prevalence between cirrhotic patients with and without upper gastrointestinal bleeding - Delvone Almeida; Antônio A Lopes; Rogerio Santos-Jesus; Igelmar Paes; Helito Bittencourt; Raymundo Paraná (Brazilian Journal of Infectious Diseases)
Bacterial infection is a frequent complication in patients with chronic liver disease, mainly during the advanced stages. There is evidence that the main factors that contribute to a predisposition to infection in cirrhotic patients are related to hepatic failure with consequent immunodeficiency. Invasive procedures (diagnostic or therapeutic) can predispose to bacterial infections, and upper gastrointestinal bleeding (UGB) is considered a potentially important risk factor. A group of cirrhotic patients (child B and C Pugh groups ) were evaluated retrospectively by chart reviews regarding the prevalence of bacterial infection during hospitalization to determine whether UGB was a risk factor. An infection was considered present if a specific organ system was identified or if fever (>38ºC) persisted for more than 24 hours with associated leukocytosis. Spontaneous bacterial peritonitis was based on classical criteria. Eighty-nine patients were evaluated. Fourty-six patients presented with UGB, and 43 patients had no UGB (control). There were infections recorded in 25/46 (54%) patients with UGB, and 15/43 (35%) in those without UGB (p=0.065). The ratio of the number of infections/admitted patients, was significantly larger in the group with UGB (0.78 ± 0.89 vs. 0.39 ± 0.62; p=0.028) since patients had more than one infection. In the UGB group compared to non UGB group, ascites was more frequent (67% vs. 42%; p=0.027); they were more likely to have undergone endoscopic procedures (p<0.001) and the mean ± SD for platelets count was smaller (96,114 ± 57,563 vs. 145,674 ± 104,083; p=0.007). The results show that UGB is an important contribution to bacterial infection among Child B and C cirrhotic patients.